PS-P03-5: QUALITATIVE INSIGHTS INTO THE BARRIERS TOWARDS BLOOD PRESSURE SCREENING, TREATMENT ADHERENCE AND LIFESTYLE MODIFICATIONS IN SINGAPORE. (January 2023) - Lwin, May Oo; Malik, Shelly; Lim, Fann; Kang, Vernon
Abstract : In Singapore, despite numerous blood pressure (BP) campaigns, hypertension prevalence amongst adults has increased to 35%, exceeding the global rate of 31.1%. In light of the worrying trend, this research aims to examine major barriers faced by Singapore residents in their management of BP health. Through a novel reverse socialisation program, the study reached out to at-risk family members through their children and employed an in-depth qualitative lens to gain meaningful insights into the barriers faced at various stages of BP management care. An intergenerational hypertension education program was launched among Singapore grade 5 students. Students were educated about hypertension and taught how to utilize a BP monitor. They then shared their knowledge and measured their family members BP at home. Family members found with borderline or high BP were invited for an interview and had their BP measurements validated by a medical professional. In-depth semi-structured interviews were conducted with 15 adults who were identified to have borderline hypertension or hypertension. Transcripts were analysed using the constant comparative approach, an analytic strategy based on grounded theory. The study identified varying personal, psychosocial, and/or external barriers faced at three different stages of BP management care - regular screening, medical adherence and lifestyle modifications (Table 1). Firstly, a major barrier towards regular BP screening was low perceived need to seek medical care due to a lack of physiological symptoms, suggesting that many respondents perceived themselves as being less susceptible to hypertension. Secondly, barriers towards medical adherence were especially a concern for diagnosed hypertensives. A dominant factor was a lack of self-efficacy in following-up with the required care, such as fear of failing doctors expectations in follow-up appointments, lack of time and inability to comply with prescribed sudden changes to dietary and exercise habits Thirdly, the inability to comply with recommended lifestyle modifications was nuanced by various factors related to ones identity such as age, job, familial obligations and culture. The in-depth qualitative perspectives revealed a complex web of barriers to BP screening, adherence and lifestyle modifications. These have important implications for future health intervention designs. Particularly, health education and communication to at-risk communities require tailored interventions to overcome the varied personal, psychosocial, and external gaps at different stages of hypertension management care. For instance, threat-framed messages could be more effective in tackling the barrier of low perceived susceptibility to hypertension, while coping-framed interventions may be better suited for improving self-efficacy for treatment adherence.